2015
DOI: 10.1021/la504041f
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Gold Nanorods with Tunable Longitudinal Surface Plasmon Resonance Peaks by Reductive Dopamine

Abstract: Hydroxyphenol compounds are often used as reductants in controlling the growth of nanoparticles. Herein, dopamine was used as an effective reductant in seed-mediated synthesis of gold nanorods (GNRs). The as-prepared GNRs (83 × 16 nm) were monodisperse and had a high degree of purity. The conversion ratio from gold ions to GNRs was around 80%. In addition, dopamine worked as an additive. At a very low concentration of hexadecyltrimethylammonium bromide (CTAB; 0.025 M), thinner and shorter GNRs (60 × 9 nm) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
109
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(118 citation statements)
references
References 40 publications
9
109
0
Order By: Relevance
“…Other studies have shown that the use of binary surfactant mixtures in the presence of aromatic additives such as salicylate‐based sodium salts and organic acids produce broad AR tunability and improve the monodispersity of nanorods . Also, the replacement of ascorbic acid by hydroquinone and dopamine has enabled a near 100% reduction yield of gold ions and the decrease in cetyltrimethylammonium bromide (CTAB) concentrations to as low as 25 mM level, respectively ,. However, few seed‐mediated protocols form AuNRs with small dimensions and width under 10 nm which are highly desirable for biomedical applications .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that the use of binary surfactant mixtures in the presence of aromatic additives such as salicylate‐based sodium salts and organic acids produce broad AR tunability and improve the monodispersity of nanorods . Also, the replacement of ascorbic acid by hydroquinone and dopamine has enabled a near 100% reduction yield of gold ions and the decrease in cetyltrimethylammonium bromide (CTAB) concentrations to as low as 25 mM level, respectively ,. However, few seed‐mediated protocols form AuNRs with small dimensions and width under 10 nm which are highly desirable for biomedical applications .…”
Section: Introductionmentioning
confidence: 99%
“…[19] Also, the replacement of ascorbic acid by hydroquinone and dopamine has enabled a near 100% reduction yield of gold ions and the decrease in cetyltrimethylammonium bromide (CTAB) concentrations to as low as 25 mM level, respectively. [20,21] However, few seed-mediated protocols form AuNRs with small dimensions and width under 10 nm which are highly desirable for biomedical applications. [22] In 2015, the synthesis of small AuNRs in high yield was reported by changing the ratio of seed to Au(III) ions in the growth solution to obtain AuNRs with an average width of less than 10 nm and lengths from 16 to 45 nm.…”
Section: Introductionmentioning
confidence: 99%
“…A close look at the literature reports illustrated the synthesis of branched Gold nanoparticles (AuNPs) using dopamine as reductant that has been explained by the formation of polydopamine which itself is highly branched . While others highlighted the seed mediated as well as seedless synthesis of gold nanorods using dopamine as binding agent along with other additives . Nevertheless few reports cited in the literature do not endorse the formation of varieties of shapes of AgNPs while using dopamine in alkaline aqueous medium, but in the present work a variety of shapes of AgNPs viz., spherical, quasi spherical, truncated triangle, hexagon, rods etc.…”
Section: Resultsmentioning
confidence: 98%
“…34 AuNRs with different ARs have different absorption wavelengths that can be used for a variety of purposes, such as PTT. 35,36 However, because of some drawbacks of NIR PTT, the RF irradiation has been used in this study for AuNRs-based hyperthermia.…”
Section: Results and Discussion Characterization Of Aunrsmentioning
confidence: 99%